VALIDITAS HASIL PENGUJIAN KADAR TIMBAL SECARA KOMPLEKSOMETRI TERHADAP MODIFIKASI TEKNIK PREPARASI DALAM PRODUK KONSENTRAT TIMBAL SULFIDA - Aprillianto, Yesaya; Hardian, Arie; Herawati; Tirta, Ardina Purnama (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Lead sulfide (PbS) concentrate is derived from the sulfide mineral galena. In nature, galena must first undergo a concentration process to become PbS concentrate. The determination of lead (Pb) content in the PbS concentrate is carried out using complexometric methods, referring to the modified ISO 13545:2000 standard during the preparation stage. In this research, the validity of the test results was assessed using several parameters, including precision test (repeatability and reproducibility), accuracy (%recovery) and estimation of measurement uncertainty. Certified reference material (CRM) Pb353, with a Pb content range of 58.20-64.33% was used as a sample in this study. The results showed an average Pb content of 61.11% for analyst A and 61.00% for analyst B in CRM Pb353. The research successfully met the precision testing requirements for repeatability (RSD 0.46% for analyst A and 0.39% for analyst B < 2/3 coefficient variance (CV) Horwitz 1.44%) and reproducibility (F-test 1.34 < F-table 4,28 and P-value 0.37 > significance level 0.05). Accuracy was also demonstrated with %recovery (analyst A 9.06–100.53% and analyst B 99.23–99.98%), as well as the estimation of measurement uncertainty (μrelative 2.27% < 5%). Therefore, the determination of Pb content using complexometric methods with modified preparation techniques in the PbS concentrate ensures the validity of the results.